Racial Disparities in Intimate Partner Violence and in Seeking Help With Mental Health. (November 2015) - Cheng, Tyrone C.; Lo, Celia C.
Applying Aday and Andersen's health services utilization model, this examination of racial disparities in women's experience of intimate partner violence also looked at racial disparities in mental disorders and in use of mental health professionals' help. We conducted a secondary data analysis of 6, 589 women completing the National Violence Against Women Survey. Per our linear regression results, minority women, versus White, tended proportionally to seek less help from mental health professionals. Help seeking by African American women was less likely if they were using illegal drugs; among Hispanic women, additional threats from partner curtailed help seeking from mental health professionals. "Other ethnic minority" women's help seeking decreased with their use of stimulants. Implications for intervention are discussed.